Beating the blues - Thase, Michael E. (Oxford University Press, 2004)
In Beating the Blues, Thase and Lang show how chronic mild depression can be relieved by learning strategies that help sufferers to recognize and change negative and distorted thinking patterns that lead to a downward spiral of pessimism. They reveal that a combination of medication and therapy has been shown to be the most effective treatment for mild depression, with an impressive 85% of patients experiencing full relief